Relationship between defense styles and neurochemical variables of the hippocampus in patients with obsessive-compulsive disorder - Atmaca, Murad; Gurok, Mehmet Gurkan; Tabara, Muhammed Fatih; Yildirim, Hanefi (Cambridge Univ Press, 2024)
This study aims to assess the correlation between NAA (N-acetyl-l-aspartate), CHO (choline), and CRE (creatine) levels in the hippocampus regions of individuals suffering from obsessive-compulsive disorder (OCD) and defensive styles of the ego.The study group was composed of twenty patients with OCD and twenty healthy controls. NAA, CHO, and CRE values in the hippocampal region using proton magnetic resonance spectroscopy (1H-MRS) were measured. Participants' defense styles were ascertained by administering the Defense Style Questionnaire-40.The patient group's NAA levels were considerably lower than the control group's on both sides of the hippocampus. The levels of CHO and CRE did not significantly differ between the two groups. The following statistically significant correlations were discovered: in the comparison group, there were negative correlations between the scores of mature defense styles and the right and left CHO levels, as well as between the immature defense mechanism scores and the right NAA levels in both the patient and control groups. In the patient group, there were also negative correlations between the left NAA values and the scores of mature defense styles.OCD patients have lower levels of NAA in the hippocampus. To validate and extend the current findings, more research involving a greater sample size is required.
Keywords: Magnetic resonance spectroscopy; defense styles; N-acetylaspartate; obsessive-compulsive disorder; choline